Social security obligations in the outsourcing scheme (subcontracting) in Hermosillo - Báez Juvera, Mayra Alejandra (Posgrados de la División de Ciencias Económica Administrativas, 2021)
This presentation will highlight the relevant points about the obligations in constitutional, legal and social matters that must be held by contracting companies and contractors. We will know the social security obligations established in our Mexican Constitution of the United States of Mexico, in the Federal Labor Law, in the Social Security Law and the Law of the Institute of the National Housing Fund for Workers. Finally, we will analyze the problems and objectives for the correct analysis of labor subcontracting companies in Hermosillo, Sonora.